Effect of Drying Techniques on Durian Seeds Biopolymer Characteristics as a Sustainable Co-Nutrient and Encapsulating Agent For Probiotics - Ahmad Naim Bin Rohaizan (Universiti Sains Islam Malaysia, 2025)
Matric: 3201130 (FST)